Prediction of torsional buckling behaviour of single-walled SiC nanotubes based on molecular mechanics. Issue 6 (3rd August 2015) - Ansari, Reza; Mirnezhad, Mahdi; Rouhi, Hessam; Bazdid-Vahdati, Majid
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Based on the molecular mechanics approach, the purpose of this paper is to analytically investigate the torsional buckling behavior of single-walled silicon carbide nanotubes (SiCNTs) with different values of diameter and chiral angles. Design/methodology/approach – To this end, the mechanical properties and atomic structure of a silicon carbide (SiC) sheet are evaluated based on the density functional theory (DFT) within the framework of the generalized gradient approximation. After that force constants of the total potential energy are theoretically obtained through establishing a linkage between the viewpoints of the quantum mechanics and molecular mechanics. Explicit expressions are presented to obtain the critical buckling shear strain corresponding to different types of chirality. The present model is capable to calculate the torsional buckling behavior of SiCNTs related to various chiral angles. The critical buckling shear strain is obtained for various types of chirality and compared with each other. Findings – It is concluded that for all diameters, zigzag nanotubes are more stable than armchair ones. Besides it is found that the minimum critical buckling shear strain is for nanotubes with (n, n/2) chiral vector. Originality/value – Investigating the torsional buckling behavior of single-walled SiCNTs with different values of diameter and chiral angle. Obtaining the mechanical properties and atomic structure of the SiC sheet based on the DFT calculations. Establishing a linkage between the molecular mechanics and quantum mechanics and obtaining the force constants of the molecular mechanics. Presenting the closed-form expression to calculate the critical buckling shear strain of single-walled SiCNTs corresponding to various types of chirality.